Functional messenger RNAs are produced by SP6 in vitro transcription of cloned cDNAs. - Krieg, P A (1984)
We describe a method for the synthesis of microgram quantities of eucaryotic messenger RNAs. Injection into the cytoplasm of frog oocytes and addition to wheat germ extracts show that these synthetic RNAs function efficiently as messenger RNAs. We confirm that a 5' cap on the mRNA is essential for translation in injected oocytes and show that most of the 3' flanking region, including the poly A tail, can be deleted without the abolition of protein synthesis. The method of mRNA synthesis involves in vitro transcription of cDNAs which have been cloned into SP6 vectors (described in the accompanying paper). This method enables one to produce large amounts of mRNA and consequently protein from any cDNA clone.